Antibacterial Efficacy of Liposomal Formulations Containing Tobramycin and N-Acetylcysteine against Tobramycin-Resistant Escherichia coli, Klebsiella pneumoniae, and Acinetobacter baumannii - Reem E. Alarfaj; Manal M. Alkhulaifi; Ahmed J. Al-Fahad; Shokran Aljihani; Alaa Eldeen B. Yassin; Majed F. Alghoribi; Majed A. Halwani (MDPI AG, 2022)
The antibacterial activity and biofilm reduction capability of liposome formulations encapsulating tobramycin (TL), and Tobramycin-N-acetylcysteine (TNL) were tested against tobramycin-resistant strains of E. coli, K. pneumoniae and A. baumannii in the presence of several resistant genes. All antibacterial activity were assessed against tobramycin-resistant bacterial clinical isolate strains, which were fully characterized by whole-genome sequencing (WGS). All isolates acquired one or more of AMEs genes, efflux pump genes, OMP genes, and biofilm formation genes. TL formulation inhibited the growth of EC_089 and KP_002 isolates from 64 mg/L and 1024 mg/L to 8 mg/L. TNL formulation reduced the MIC of the same isolates to 16 mg/L. TNL formulation was the only effective formulation against all A. baumannii strains compared with TL and conventional tobramycin (in the plektonic environment). Biofilm reduction was significantly observed when TL and TNL formulations were used against E. coli and K. pneumoniae strains. TNL formulation reduced biofilm formation at a low concentration of 16 mg/L compared with TL and conventional tobramycin. In conclusion, TL and TNL formulations particularly need to be tested on animal models, where they may pave the way to considering drug delivery for the treatment of serious infectious diseases.